2013
DOI: 10.1093/bja/aes474
|View full text |Cite
|
Sign up to set email alerts
|

Problems in obtaining sufficient anaesthesia with propofol and remifentanil: three cases, a test infusion, and a review

Abstract: The potential causes of this effect are discussed. We advise clinicians to be aware of this unusual response to remifentanil. If such a response is suspected, we recommend the use of another opioid. If this is suspected before GA, we propose the use of our test as a diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(15 reference statements)
2
3
0
Order By: Relevance
“…A lack of clinical effect closer to that which we observed has recently been described in adults [9]. Bache reported three adult patients who, over a five year period, underwent seven anaesthetics between them where they did not appear to demonstrate the normal clinical effect of remifentanil.…”
Section: Discussionsupporting
confidence: 81%
“…A lack of clinical effect closer to that which we observed has recently been described in adults [9]. Bache reported three adult patients who, over a five year period, underwent seven anaesthetics between them where they did not appear to demonstrate the normal clinical effect of remifentanil.…”
Section: Discussionsupporting
confidence: 81%
“…The present results showed that remifentanil induced more stable hemodynamics than sufentanil . This difference in hemodynamics may be associated with the more effective dose‐dependent inhibition of sympathetic activity by remifentanil than by other opioids …”
Section: Discussionsupporting
confidence: 49%
“…In a patient who was treated for narcolepsy with modafinil, inhalation anesthetics had to be used because anesthesia could not be achieved (BIS was 72) after induction with 6 mg/kg of propofol[ 3 ]. Bache et al [ 4 ] reported insufficient anesthetic effects of propofol and remifentanil for general anesthesia in three cases over 5 years and suspected the possibility of acute tolerance to remifentanil. In this case, the patient had no medical or drug history and the BIS decreased to 35 after the administration of IV anesthetics; therefore, resistance to propofol and acute tolerance to remifentanil can be excluded.…”
Section: Discussionmentioning
confidence: 99%